Analisis Personal Branding Sherly Tjoanda pada Pilkada Provinsi Maluku Utara 2024 di Media Sosial Instagram @s_tjo - Ria Nita Anggreani; Gabid Hanife (Universitas Muhammadiyah Jember, 2025)
The utilization of social media as a tool for building political image has become a crucial strategy in regional elections. This study aims to analyze Sherly Tjoanda’s personal branding during the 2024 North Maluku gubernatorial election through her Instagram account @s_tjo. The research is grounded in Peter Montoya’s theory of personal branding, particularly the eight laws of personal branding: specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. This theoretical framework serves as the foundation for assessing the consistency and effectiveness of political self-image presented through social media. Employing a qualitative approach with content analysis as the method, the study collects data from Instagram posts, focusing on visual and narrative elements that represent Sherly Tjoanda’s political image. The analysis emphasizes campaign content such as photos, videos, captions, and forms of interaction with followers to uncover the patterns of political communication established through personal branding. The findings reveal that Sherly Tjoanda’s personal branding strategy demonstrates a structured, authentic, and differentiation-based approach. She highlights her identity as a female gubernatorial candidate by projecting maternal values and emotional closeness with the public. The use of the tagline “Coblos yang Cantik” (“Vote for the Beautiful One”) serves as a smart political differentiator. Additionally, she frames herself as a “Mother” to the people of North Maluku, reinforcing emotional resonance with voters, particularly women.